Adherence to growth hormone therapy in children with growth hormone deficiency: Experience at a public sector tertiary care hospital - Hina Sattar, Aqeela Ayub, Rehmana Waris, Jaweria Zain, Hina Hanif, Abdul Malik (Journal of Rawalpindi Medical College, 2022)
Objective: To determine the adherence rate of recombinant human Growth Hormone therapy (rhGH) in children suffering from growth hormone deficiency and parent’s perspectives regarding reasons for non-compliance. Materials and Methods: This study was conducted at District Headquarters Hospital, Rawalpindi from January 2020 to June 2021. All children already diagnosed with Growth hormone deficiency were included in the study. Children with less than one-year duration of treatment were excluded. Demographic details were recorded on a predesigned proforma. Adherence to treatment was assessed using a combination of methods based on previous studies. The proportion of days covered >80% was taken as good adherence. Data was entered and analyzed in SPSS 25. Qualitative variables such as gender, socioeconomic status, source of growth hormone injections, and adherence were presented as frequency and percentages. Self-reported reasons for non-adherence were presented as frequency and percentage. Results: A total of 38 patients meeting the inclusion criteria were included in the study. Both genders were equal in number. The mean age at diagnosis was 8.2 ± 3.6 years. Socioeconomic status was the middle (upper or lower) in 55% of the cases while 45% belonged to the lower socioeconomic group. Adherence was good in 44% of the patients while suboptimal in 56%. The cost of treatment was the main reason for non-adherence in all the cases. Conclusion: Non-adherence to rhGH therapy is common in our setup. Clinicians should be aware of different factors affecting adherence and all efforts should be made to ensure good adherence so that optimal targets may be achieved. Keywords: Adherence, Growth hormone therapy, socioeconomic status